Assembly, photography, mirror: Waldemar Cordeiro after concretism - Fabris, Annateresa (PORTO ARTE: Revista de Artes Visuais, 2017)
In search of new possibilities for concretism, Cordeiro becomes interested in the “brutal realism” of the urban landscape, in which he detects a creative principle rooted in the dialectical process of the montage. Resulting of this new moment (1964-1965), the “popcretos” are often characterized by the use of photographic images, presented as rhetorical and ideological operations. Used also in later works, photography becomes an instrument to challenge traditional ideas about art, having the transformations arisen by the presence of mass media as horizon.